PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V B SDN 94 PEKANBARU - Sari, Mutia Yulita Sari Yulita; Alpusari, Mahmud Alpusari Mahmud; ', Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : background of this study is the lowoutocomes of natural science(IPA) of the fourth grade students of V B SDN 94 Pekanbaru, with the average score ofthe class is 67,60. Based on the standard minimum criteria (KKM) 72 which has beendetermined by the school, there were 17 students are below the standard minimumcriteria or 48,57% from overal number of 35 students. This research is an actionsresearch which aims to enhance learning outocomes natural science (IPA) gradestudents of V B SDN 94 Pekanbaru with the implementation of cooperative leaningmodel Type Student Teams Achievement Division (STAD). Formulation of the problem:does cooperative leaning model Type Student Teams Achievement Division (STAD) canimprove natural science learning autocome grade students of V B SDN 94 Pekanbaru?.This research was carried out on 17 April 2015 until 8 May 2015 with II cycles. Thesubject of this research is grade students of V B SDN 94 Pekanbaru with total number35 students who were bacame the participants of this research. Data collectioninstruments in this research are teacher and studets activity sheets as well as a writtentest sheet. The result of this research can bee seen from the result of the study before theimplementation of cooperative leaning model Type Student Teams AchievementDivision (STAD) are given which the average score 67,60 after the action is given orafter implementation of cooperative leaning model Type Student Teams AchievementDivision (STAD) are increased in cycle I, with an average score 81,60 which areincreased as much as 20,17% and cycle II the average score 85,37 which are increasedas much as 26,28%. It can be concluded that the cooperative leaning model TypeStudent Teams Achievement Division (STAD) can improve natural science (IPA)learning process with the increasing of the learning outocomes of fourth grade studentsof V B SDN 94 Pekanbaru in learning natural science (IPA)Key Words : Cooperative Leaning Model Type Student Teams Achievement Division(STAD), IPA Study Results.